Heat shock proteins 70 as markers of complications in children with acute lymphoblastic leukemia - Tetiana KONDRATIUK; Yuriy ODINETS; Tetiana GORBACH; Victoria KOVAL (Archives of the Balkan Medical Union, 2020)
Introduction. The mortality rate from complications of acute lymphoblastic leukemia (ALL) in children is high and exceeds the mortality rate from relapse of leukaemia. Ultrahigh expression of HSP 70 is associated with treatment resistance and is an adverse clinical outcome in ALL in children.